Performance of Cauliflower Genotypes for The Early Season Production in Pokhara, Kaski, Nepal - Lohani, Santosh; Adhikari, Saroj; Bhusal, Yubaraj; Subedi, Sujan; Pradhan, Navin Gopal; Ranabhat, Siddanta (Nepalese Horticulture, 2024)
A field experiment was conducted from July to November for three consecutive years; 2019, 2020, and 2021 to identify the cauliflower genotypes suitable for early planting under Pokhara conditions. In 2019, the five cauliflower genotypes (Ageni, Khumal Jyapu 1, Khumal Jyapu 2, Terai 1, Terai 2) from the National Horticulture Research Center were evaluated in the non-replicated design with the check variety White Cup (F1), and in the year of 2020 and 2021 five genotypes of Cauliflower named Terai 1, Terai 2, Ageni, Pusa Sarad, and White Cup(F1) were evaluated in a randomized complete block design (RCBD) with four replications. The four-week-old seedlings were transplanted in the field in the first week of August. From the pooled mean of two years (2020 and 2021) of experiments, there were significant differences among the cauliflower genotypes for days to harvest, curd weight, curd diameter, and curd height and yield. The highest curd weight was found for White Cup (405.79 g) which was at par with Terai 2 (396.21 g). The earliest genotype of cauliflower ready for harvest was White Cup (57.75 DAT) which was statistically similar to Terai 1 (60.12 DAT) followed by Terai 2 (65.25 DAT) and the highest yield was found for Terai 2 (18.55 t/ha) which was at par with White Cup (18.14 t/ha) and Terai 1(16.15 t/ha). Based on the three-year results, two open-pollinated genotypes; Terai 1 and Terai 2 are promising for August planting in Pokhara condition.